2010
DOI: 10.1111/j.1469-0691.2009.03042.x
|View full text |Cite
|
Sign up to set email alerts
|

A variant of the Southern German clone of methicillin-resistant Staphylococcus aureus is predominant in Croatia

Abstract: The aim of the present study was to investigate the antibiotic susceptibility patterns and molecular epidemiology of clinical methicillin-resistant Staphylococcus aureus (MRSA) isolates recovered in 24 hospitals in 20 cities in Croatia from October to December 2004. A total of 1815 consecutive S. aureus isolates were recovered, 248 of which were MRSA. The MRSA isolates were analysed using spa typing, multilocus sequence typing and SCCmec typing. Furthermore, the presence of Panton-Valentine leukocidin (PVL) ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
23
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 29 publications
11
23
3
Order By: Relevance
“…In this study, methicillin resistance was detected in 90.5% S. aureus isolates. The high frequency of MRSA isolates in the present study was in agreement with the findings of the studies in Iran (1), Bolivia (18), and India (19) and is higher than Hungary (20) and Croatia (21). The results of the susceptibility testing showed that all the isolates were susceptible to vancomycin, linezolid, and teicoplanin which is consistent with a previous study in Iran (1) and other studies (16)(17)(18)(19)(20)(21).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In this study, methicillin resistance was detected in 90.5% S. aureus isolates. The high frequency of MRSA isolates in the present study was in agreement with the findings of the studies in Iran (1), Bolivia (18), and India (19) and is higher than Hungary (20) and Croatia (21). The results of the susceptibility testing showed that all the isolates were susceptible to vancomycin, linezolid, and teicoplanin which is consistent with a previous study in Iran (1) and other studies (16)(17)(18)(19)(20)(21).…”
Section: Discussionsupporting
confidence: 82%
“…They showed that the most commonly detected antibiotic resistance genes in the MRSA strains were tetK (89.18%), mecA (71.62%), msrA (56.75%), and tetM (54.05%). In accordance with the results of the studies in Italy (35), Croatia (21), and Hungary (20), a high resistance to ciprofloxacin was seen in the current study (63.2%), which could be due to the widespread use of ciprofloxacin in the treatment of MRSA infections, mutation in gyrase or topoisomerase IV enzymes, and efflux pumps (36).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…According to the literature, MRSA strains are resistant not only to beta-lactams but also to macrolides, lincosides, and aminoglycosides (6,8,18). In the present study, the majority of the MRSA isolates were resistant to ampicillin (100%), ciprofloxacin (94.5%), gentamicin (98.2%), erythromycin (90.9%), tetracyclin (87.3%), and clindamycin (98.2%), which is in line with the findings reported in Iran (8), Croatia (17), and Turkey (19). The rate of resistance to tested antibiotics, with the exception of amikacin among MRSA isolates, was higher than those among MSSA isolates, which is in accordance with the findings reported by Yu et al (20).…”
Section: Discussionsupporting
confidence: 81%
“…Overall, it is well established that isolation rate of S. aureus in UTI is between 2% and 15% (5). In the present study, MRSA screening showed that 61.1% of the tested isolates were confirmed to be MRSA, which was lower than those reported in previous studies from Iran (8), and higher than those reported in Croatia (17). Moreover, different prevalence rates are reported for MRSA by different researchers.…”
Section: Discussioncontrasting
confidence: 54%